2018
DOI: 10.3892/mmr.2018.9635
|View full text |Cite
|
Sign up to set email alerts
|

Genistein attenuates renal fibrosis in streptozotocin‑induced diabetic rats

Abstract: The present study aimed to investigate the antifibrogenic effects of genistein (GEN) on the kidney in streptozotocin (STZ)-induced diabetic rats and to determine the associated mechanisms. Rats were randomized into four groups: Normal control (N), STZ (S), L (STZ + low-dose GEN) and H (STZ + high-dose GEN). After 8 weeks, the fasting blood glucose (FBG) level, the ratio of kidney weight to body weight (renal index), 24-h urine protein, blood urea nitrogen (BUN), serum creatinine (SCr), renal total antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 50 publications
5
27
0
Order By: Relevance
“…Our data are in agreement with previous findings that showed streptozotocin (STZ)-induced diabetic rats caused increased MDA level that reflect the levels of tissue lipid peroxidation and decreased SOD activity that scavenge superoxide products in kidney tissue [36]. Glucose is oxidized to reactive ketoaldehyde and superoxide radicals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are in agreement with previous findings that showed streptozotocin (STZ)-induced diabetic rats caused increased MDA level that reflect the levels of tissue lipid peroxidation and decreased SOD activity that scavenge superoxide products in kidney tissue [36]. Glucose is oxidized to reactive ketoaldehyde and superoxide radicals.…”
Section: Discussionsupporting
confidence: 93%
“…Past investigations announced that diabetic rats indicated essentially expanded serum uric acid (SUA), serum creatinine (SCr), and urea nitrogen (BUN) levels [35] and [36].…”
Section: Discussionmentioning
confidence: 99%
“…(i) Western blotting showed phospho-PRDX1 (p-PRDX1) expression in control and HG after transfer DcR2 siRNA or (continued) the specific PTK inhibitor genistein. 37 These results suggest that DcR2 regulates the phosphorylation of PRDX1 through the "bridge" of PTK.…”
Section: Discussionmentioning
confidence: 86%
“…As shown in Figure 8k and l, PRDX1 phosphorylation levels were markedly inhibited by genistein, a specific inhibitor of PTK. 37 These data suggest that DcR2 regulates the phosphorylation level of PRDX1 through PTK.…”
Section: Dcr2 Regulates the Level Of Prdx1 Phosphorylationmentioning
confidence: 82%
“…Jia et al reported that the rats were given with genistein can attenuate renal fibrosis in STZ-induced diabetic rats. Supplementation with genistein for 8 weeks also increased endogenous antioxidant superoxide dismutase and decreased lipid peroxidase and malondialdehyde (MDA) [22]. also reported that supplementation on early stage of diabetic-induced renal damage can decrease level of inflammation markers such as nuclear factor kappa B (NFκB), tumor necrosis factor α (TNF-α), dan cyclooxygenase-1 (COX-1) [23].…”
Section: Comparison Of Renal Tubules Necrosis In Rats Given With Blacmentioning
confidence: 93%